2004
DOI: 10.1271/bbb.68.584
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Effect of Ingesting Tannic Acid on the Absorption of Iron, but Not of Zinc, Copper and Manganese by Rats

Abstract: Interest in the beneficial effects of polyphenols, including tannic acid (TA), is increasing, although, these compounds also have adverse effects; for example, on the absorption of iron (Fe), and possibly other trace minerals. We examined the effect of a graded dose of TA on the absorption of Fe and compared with that of zinc (Zn), copper (Cu) and manganese (Mn) in rats. We also investigated the effect of TA on cecal fermentation which plays a role in absorption. In Experiment 1, to set the optimum dose of Fe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 30 publications
7
59
0
2
Order By: Relevance
“…These results were consistent with the studies of Cook et al (1995) and Marouani et al (2007) that showed that red wine, tea and other beverages rich in polyphenolic compounds inhibited the absorption of non-heme iron. In addition, in line with our results, supplementation of tannic acid (gallotannin) in the diets of weanling pigs and rats induced the formation of stable polyphenol/iron complexes in the gut having a negative impact on plasma iron concentration (Afsana et al, 2004;Lee et al, 2010). Nevertheless, the precise mechanism by which bioactive dietary polyphenolic compounds inhibit iron metabolism has not been delineated.…”
Section: Discussionmentioning
confidence: 62%
“…These results were consistent with the studies of Cook et al (1995) and Marouani et al (2007) that showed that red wine, tea and other beverages rich in polyphenolic compounds inhibited the absorption of non-heme iron. In addition, in line with our results, supplementation of tannic acid (gallotannin) in the diets of weanling pigs and rats induced the formation of stable polyphenol/iron complexes in the gut having a negative impact on plasma iron concentration (Afsana et al, 2004;Lee et al, 2010). Nevertheless, the precise mechanism by which bioactive dietary polyphenolic compounds inhibit iron metabolism has not been delineated.…”
Section: Discussionmentioning
confidence: 62%
“…Afsana et al (2004) demonstrated no effect of tannin supplementation on Zn absorption in vivo. Reports of CT complexes with other cations are scarce and usually related to tea consumption.…”
Section: The Interactions Between Minerals and Condensed Tanninsmentioning
confidence: 85%
“…Condensed tannin-Fe complexes can effectively inhibit Fe absorption (Lavin et al, 2010;Wren et al, 2013) at levels as low as 5 g tannic acid/kg (Afsana et al, 2004). In cell culture, a 1:1 ratio of tannic acid to Fe inhibited 92% of Fe absorption (Glahn and Wortley, 2002).…”
Section: The Interactions Between Minerals and Condensed Tanninsmentioning
confidence: 99%
“…EFSA received directly from the applicant the technical dossier in support of this application. 6 According to Article 8 of that Regulation, EFSA, after verifying the particulars and documents submitted by the applicant, shall undertake an assessment in order to determine whether the feed additive complies with the conditions laid down in Article 5. The particulars and documents in support of the application were considered valid by EFSA as of 9 August 2011.…”
Section: Discussionmentioning
confidence: 99%